Reduced Intrinsic Connectivity of Amygdala in Adults with Major Depressive Disorder - Ramasubbu, Rajamannar; Konduru, Nithya; Cortese, Fil; Bray, Signe; Gaxiola, Ismail; Goodyear, Bradley (Frontiers in Psychiatry, 2014)
Imaging studies of major depressive disorder (MDD) have demonstrated enhanced resting-state activity of the amygdala as well as exaggerated reactivity to negative emotional stimuli relative to healthy controls. However, the abnormalities in the intrinsic connectivity of the amygdala in MDD still remain unclear. As the resting-state activity and functional connectivity (RSFC) reflect fundamental brain processes, we compared the RSFC of the amygdala between unmedicated MDD patients and healthy controls. Seventy-four subjects, 55 adults meeting the DSM IV criteria for MDD and 19 healthy controls, underwent a resting state 3-T functional magnetic resonance imaging (fMRI) scan. An amygdala seed-based low frequency RSFC map for the whole brain was generated for each group. Compared with healthy controls, MDD patients showed a wide-spread reduction in the intrinsic connectivity of the amygdala with a variety of brain regions involved in emotional processing and regulation, including the ventrolateral prefrontal cortex, insula, caudate, middle and superior temporal regions, occipital cortex, and cerebellum, as well as increased connectivity with the bilateral temporal poles (p< 0.05 corrected). The increase in the intrinsic connectivity of amygdala with the temporal poles was inversely correlated with symptom severity and anxiety scores. Although the directionality of connections between regions cannot be inferred from temporal correlations, the reduced intrinsic connectivity of the amygdala predominantly with regions involved in emotional processing may reflect impaired bottom-up signaling for top-down cortical modulation of limbic regions leading to abnormal affect regulation in MDD.